Advanced hybrid energy storage system - Yeo, Yeow Leong (2015)
As the population grows and technologies advances, the usage of energy in daily life grows aggressively [11] which in turn, cause the depletion of natural resources at an alarming rate. Therefore, alternative resources are crucial to the survival of the current world. Many researches and studies are being focused on renewable energy sources as they are replenishable. One of the commonly covered topics is the usage of solar energy. Photovoltaic systems convert solar energy into electrical power. This system is sustainable and environmental friendly but it has shortcomings too. As the main and only source of supply is solar energy, the input power of the PV system cannot be accurately predicted. On top of that, the weather condition is not guaranteed. Therefore, energy storage is essential to help improve the efficiency of the PV system. One of the most favourable components used as an energy storage device is lithium-ion battery which has high energy density and is able to handle slow moving power fluctuations. However, lithium-ion has a very slow response speed and it is unable to deal with power with high frequency components. Thus, by incorporating another device that can handle high frequency components with the lithium-ion battery, the disadvantage of the lithium-ion battery will be mitigated. This forms a Hybrid Energy Storage System and it combines the advantages of two energy storage devices and optimises the system efficiency. A research paper [1] shows an efficient method in controlling the HESS. It is simulated and proven to be better than some other conventional ways of power allocation between the two energy storage units. Hence, a hardware configuration should be tested to support the paper. The experiment was done for only the battery bank while the ultra-capacitor and HESS are yet to be tested. Nevertheless, the results from the battery experiments achieved are promising.